Gradient estimates for the double phase problems in the whole space - Bei-Lei Zhang; Bin Ge (Electronic Research Archive, 2023)
This paper presents Calderón-Zygmund estimates for the weak solutions of a class of nonuniformly elliptic equations in $ \mathbb{R}^n $, which are obtained through the use of the iteration-covering method. More precisely, a global Calderón-Zygmund type result